Teak Leaves as Wrapping for Beef/Goat Meat in Green Qurban 1444 H at Universitas Syiah Kuala - Tedy Kurniawan Bakri; Jumadil Akhir; Allaily Allaily; Geubrina Maghfirah; Rahmilia Hadiyani; Rina Suryani Oktari (Departemen of Animal Science, Agriculture Faculty, Syiah Kuala University, 2023)
The use of plastic materials as packaging for Qurban (refers to the act of sacrificing an animal during the Islamic festival of Eid al-Adha) meat is indeed more practical, but its characteristic of being non-biodegradable poses environmental problems. Therefore, an alternative packaging solution using plant leaves needs to be explored. Teak leaves, a forestry plant, contain antimicrobial properties that can inhibit the growth of pathogens, thus extending the shelf life of meat at room temperature. This approach has a positive impact on the distribution of Qurban meat, as it maintains quality while being environmentally safe. The utilization of teak leaves as wrapping material for meat is a part of the Green Qurban 1444 H activity at Universitas Syiah Kuala (USK) in Banda Aceh. The committee is responsible for managing a total of 11 goats and 9 cows, with the meat distributed among 13 villages, resulting in 578 portions. The teak leaves used for wrapping correspond to the respective meat portions. In conclusion, the use of teak leaves in the Green Qurban 1444 H activity at USK serves the dual purpose of supporting the environmentally friendly concept by replacing plastic and maintaining the quality of the meat.